Peran Komite Madrasah Dalam Pelaksanaan Manajemen Berbasis Madrasah (MBM) di MAN 1 Pringsewu - Achmad Dimas Cahyadin; Ahmad Fauzan; Riyuzen Praja Tuala (El-Idare, 2022)
This research is motivated by the role of the madrasah committee in implementing Madrasa-Based Management at MAN 1 Pringsewu. The role of the school committee in relation to improving the quality of education services is as a giver of consideration, support for education service activities, controller of education service activities, a liaison or hook of communication ropes between the community and the government. This study uses a qualitative descriptive method, the location in this study is at MAN 1 Pringsewu and the data sources used are primary data and secondary data and there are several techniques used in collecting data, namely observation, interviews, and documentation. In this study, the authors also use triangulation techniques sources and techniques. Based on the results of this study it can be concluded that the role of the Madrasa committee at MAN 1 Pringsewu has carried out its role well, namely by means of the school committee as a giver of consideration in every plan and program prepared by the school, the school committee as a supporter of implementing and improving the quality of education at MAN 1 Pringsewu in the form of financial support, energy, and mental support. The school committee exercises control over decision making and education planning in schools, the school committee acts as a liaison or hook of communication between the community and the government.